Disease-modifying activity of progesterone in the hippocampus kindling model of epileptogenesis - Reddy, Doodipala Samba (2010)
Progesterone (P) is an endogenous anticonvulsant hormone. P is being evaluated as a treatment for epilepsy, traumatic brain injury, and other complex neurological conditions. Preclinical and clinical studies suggest that P appears to interrupt epileptogenic events. However, the potential disease-modifying effect of P in epileptogenic models is not widely investigated. In this study, we examined the effects of P on the development of hippocampus kindling in female mice. In addition, we determined the role of progesterone receptors (PR) in the P’s effect on the kindling epileptogenesis utilizing PR knockout (PRKO) mice. P, at 25 mg/kg, did not affect seizures and did not exert sedative/motor effects in fully-kindled mice. P treatment (25 mg/kg, twice daily for 2 weeks) significantly suppressed the rate of development of behavioral kindled seizure activity evoked by daily hippocampus stimulation in wild-type (WT) mice, indicating a disease-modifying effect of P on limbic epileptogenesis. There was a significant increase in the rate of ‘rebound or withdrawal’ kindling during drug-free stimulation sessions following abrupt discontinuation of P treatment. A washout period after termination of P treatment prevented such acceleration in kindling. PRKO mice were kindled significantly slower than WT mice, indicating a modulatory role of PRs in seizure susceptibility. P’s effects on early kindling progression was partially decreased in PRKO mice, but the overall (~2-fold) delay in the rate of kindling for the induction of stage 5 seizures was unchanged in PRKO mice. Moreover, the acute anticonvulsant effect of P was undiminished in fully-kindled PRKO mice. These studies suggest that P exerts disease-modifying effects in the hippocampus kindling model at doses that do not significantly affect seizure expression and motor performance, and the kindling-retarding effects of P may occur partly through a complex PR-dependent and PR-independent mechanism.